The prevention of venous thromboembolism and the risk of postoperative complications in patients with rheumatoid arthritis and osteoarthritis after total hip arthroplasty - A. V. Rybnikov; E. I. Byalik; T. M. Reshetnyak; S. A. Makarov; A. E. Khramov (Научно-практическая ревматология)
Patients who have undergone large (hip, knee) joint replacement constitute a group at high risk for developing venous thromboembolic events (VTEs). According to different authors, the risk of nonpreventable VTEs in these patients varies from 40 to 80%.Objective: to analyze the incidence of VTE and the risk of postoperative wound-related bleeding and complications in patients with rheumatoid arthritis (RA) and osteoarthritis (OA) after total hip arthroplasty. Subjects and methods. The investigation enrolled 486 patients with RA (n=212) and OA (n=274) who underwent primary hip arthroplasty. Each patient group was divided into three subgroups according to prevention with the following drugs: 1) nadroparin calcium; 2) dabigatran etexilate; 3) nadroparin calcium switched to dabigatran etexilate. According to the International Society on Thrombosis and Haemostasis criteria, intra- and postoperative blood loss was assessed during the first 7 days after surgery; the wound healing process was also evaluated.Results and discussion. VTE was prevented with the drugs in 239 (49.2%) patients, 130 (26.8%) of them received nadroparin calcium, the remaining 117 (24.0%) patients had dabigatran etexilate or both drugs. Postoperative VTEs were recorded in 36 (7.4%) out of the 486 patients. VTEs were detected significantly less frequently In RA than in OA (1.2 and 6.1%, respectively; p=0.0013). VTEs were more commonly asymptomatic in both groups. No fatal bleeding was seen in any patient, which confirms the safety of anticoagulant therapy. Blood transfusions were more frequently given to bleeding patients with RA than to those with OA (14.4 and 5.7% of cases, respectively; p<0.001). The number of patients with RA who required discontinuation of anticoagulant therapy was more than those with OA (6.6% and 1.4%, respectively). Delayed wound healing was also much more common in patients with RA (n=56; 26.4%) than in those with OA (n=14; 5.1%). VTE occurred much more often in patients receiving monotherapy with nadroparin calcium than in those having combined therapy (p<0.0001), and somewhat more frequently than in those taking dabigatran etexilate (p=0.054), however, the difference for the latter did not reach statistical significance.Conclusion. During elective hip replacement, VTEs occurred less frequently in patients with RA than in those with OA (1.23 and 6.17%, respectively, p=0.0013). After hip arthroplasty, VTEs were detected significantly more often in nadroparin calcium-treated patients with RA and OA than in patients receiving combined therapy. Postoperative wound-related bleedings were significantly more frequently observed in RA than in OA (14.4 and 5.7% of cases, respectively). The risk of postoperative wound-related complications in RA is much higher than in OA (relative risk, 4.33; 95% confidence interval, 2.67–7.03; p<0.001), which increases the length of hospital stay and the cost of the treatment performed.